(untitled) (Nigerian Journal of Technology, 2020)
This paper develops a new well test analysis procedure of a horizontal well in an infinite-acting reservoir. Hitherto, horizontal well pressure drawdown test analysis during infinite-acting flow was accomplished based on a straight line method obtained from a plot of flowing wellbore pressure versus log of flow time. In that procedure, only limited system characterization was possible. Furthermore, the rigorous type curve matching was resorted to when a straight line did not appear. In the method developed here, a plot of flowing wellbore pressures, pwf, against dimensionless wellbore pressures, pD, is made for analysis. Results show that a straight line relationship exists between the two plotted parameters on a linear paper. The straight line slope across the middle time region can be taken to perform test analysis. From the plot, reservoir pressure, near wellbore permeability, reservoir capacity, fluid mobility and transmissibility can be calculated. Mathematical procedure leading to this method of analysis is based on selection of relevant source and Green’s functions for a horizontal well during infinite-acting flow and purely as a line source. A case pressure test selected for analysis using the method developed here yielded very close reservoir character compared to the reservoir being characterized. http://dx.doi.org/10.4314/njt.v39i3.22